PENGETAHUAN PAJAK DAN EVALUASI KEBIJAKAN ATAS PAJAK E-COMMERCE DAN DAMPAKNYA TERHADAP KEPATUHAN WAJIB PAJAK (STUDI KASUS GREEN SEDAYU MALL) - Stephanie Catherine; Estralita Trisnawati (Jurnal Ilmu Akuntansi, 2024)
This study examines the impact of e-commerce tax knowledge and regulation socialization on taxpayer compliance. The research is motivated by the growing use of e-commerce, which presents new challenges for tax management. Although e-commerce is becoming increasingly popular, the level of tax compliance in this sector remains low. This study explores the influence of knowledge and regulation socialization on tenant compliance at Green Sedayu Mall. Using a quantitative approach, data were collected through questionnaires from 42 respondents, consisting of tenant managers or employees. Data analysis using SPSS version 29 revealed that e-commerce tax knowledge and regulation socialization significantly affect taxpayer compliance. The findings underscore the importance of continuous tax education and effective socialization strategies to improve compliance. A combination of enhanced tax knowledge and regulation socialization can serve as a solution to boost tax compliance in the e-commerce sector. Implications for the government and tax authorities highlight the need to develop targeted education and socialization programs to raise tax awareness in the digital era. Collaboration between businesses and tax authorities is essential to create a transparent and compliant tax ecosystem.